Dysmenorrhea Among Women Living in Saudi Arabia: Prevalence, Determinants, and Impact - Mohammad A. Jareebi; Saja A. Almraysi; Dhiyaa A. H. Otayf; Ghadeer A. Alneel; Areej H. Zughaibi; Sarah J. Mobarki; Imtenan A. Oberi; Hayam A. Alzahrani; Shatha A. Aldhowaihi; Zainab A. Alramadhan; Majed A. Ryani; Ahmed A. Bahri; et al. (Life)
Dysmenorrhea, or painful menstruation, is one of the most prevalent conditions among adolescents and young females globally, significantly affecting academic performance, quality of life, and social interactions. Despite its high prevalence, dysmenorrhea has been rarely investigated in Saudi Arabia, resulting in a scarcity of national data. This study aimed to evaluate the prevalence, severity, and determinants of dysmenorrhea among females in Saudi Arabia. This cross-sectional, questionnaire-based study included 1026 participants recruited from various regions of Saudi Arabia using a convenience sampling technique. Data collection was conducted using a validated, self-administered online questionnaire. Descriptive and inferential statistics were utilized to evaluate the prevalence, severity, and associated symptoms of dysmenorrhea. Additionally, multiple logistic regression was employed to identify the determinants of dysmenorrhea within the sample. The analysis was performed using R software. The prevalence of dysmenorrhea among the sample was 87%, with a mean pain score of 6 ± 2.2. Common menstrual cycle-associated symptoms included mood swings (79%), abdominal bloating (60%), diarrhea (32%), and constipation (26%). Factors associated with an increased risk of dysmenorrhea included Saudi nationality (OR = 1.96, p = 0.032), employment (OR = 1.75, p = 0.034), and a history of gynecological surgeries (OR = 1.81, p = 0.045). Conversely, multiparity was associated with a reduced risk of dysmenorrhea (OR = 0.36, p = 0.046). Dysmenorrhea is highly prevalent among Saudi women and is accompanied by significant menstrual symptoms that adversely affect quality of life. Understanding its determinants and associated symptoms is essential for improving management strategies and mitigating its impact on women’s lives.